A Comparative Study of Virtual UI for Risk Assessment and Evaluation - Bushra, Naila; Carruth, Daniel; Deb, Shuchisnigdha (Advances in Visual Computing, 2018)
The simulation of a real-life environment in VR greatly reduces the time and cost to perform experiments. A useful application of Virtual Reality (VR) can be training employees and measuring their performances before their assignment in the real work environment. For this study, an experimental environment was created using VR to represent a machine shop in an industrial manufacturing facility. The VR provided with a safe environment for trainees to correctly identify hazards associated with each machine. A comparative study was conducted to evaluate two different ways a trainee can interact with the training system within the VR environment. Participants in the study were asked to perform training tasks with both user interfaces and complete user experience and usability questionnaires. The evaluation of interfaces played an important role in the design and selection of a useful mode of interaction within the VR environment.